2022
DOI: 10.1186/s40798-021-00386-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of Ratings of Perceived Exertion During Resistance Exercise in Healthy Participants: A Systematic Review and Meta-Analysis

Abstract: Background The validity of ratings of perceived exertion (RPE) during aerobic training is well established; however, its validity during resistance exercise is less clear. This meta-analysis used the known relationships between RPE and exercise intensity (EI), heart rate (HR), blood lactate (BLa), blood pressure (BP) and electromyography (EMG) to determine the convergent validity of RPE as a measure of resistance exercise intensity and physiological exertion, during different forms of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 113 publications
(211 reference statements)
1
25
0
2
Order By: Relevance
“…Exercise intensity [HR in beats per minute (bpm); Polar Monitor, Kempele, Finland], rate of perceived exertion (RPE, Borg's 6-20 scale) and pain (visual analogue scale, 0-10) were recorded at the end of each exercise. The methods that were used to assess the outcome measures in the present study have been shown to have high validity and reliability [32][33][34][35].…”
Section: Protocolmentioning
confidence: 84%
“…Exercise intensity [HR in beats per minute (bpm); Polar Monitor, Kempele, Finland], rate of perceived exertion (RPE, Borg's 6-20 scale) and pain (visual analogue scale, 0-10) were recorded at the end of each exercise. The methods that were used to assess the outcome measures in the present study have been shown to have high validity and reliability [32][33][34][35].…”
Section: Protocolmentioning
confidence: 84%
“…The intensity of strengthening exercises was monitored using a modified Borg Scale 28. The Borg Scale is valid tool for measuring exertion during resistance training 29 30…”
Section: Methodsmentioning
confidence: 99%
“…In a recent meta-analysis by Lea et.al, rate of perceived exertion (RPE) has been shown to be a valid measure of exercise intensity and exertion. 60 As such, utilizing RPE can be monitored to ensure sufficient load is being applied. Considering this information, a 60-80% intensity of 1RM can be estimated at about 6-8/10 or 14-17/20 using an RPE scale.…”
Section: Phase Iii: Strengtheningmentioning
confidence: 99%